The Emerging Challenges of Industrial Revolution 4.0: A Students’ Perspective - Muhammad Talhah Ajmain Jima’ain, Fatin Nabilah Abu Hassan, Khadijah Abdul Razak, Aminudin Hehsan, Juhazren Junaidi (International Journal of Advanced Science and Technology, 2020)
The Fourth Industrial Revolution (IR 4.0) has emerged as one of the most influential contributor in the development and landscape of the modern world. Students in tertiary education are expected to get out of the way to meet the challenges posed by IR 4.0. One of the fields that is affected by this wave of revolution is Education, therefore it is pertinent for a University to provide space and opportunity for future graduates to have a sense of self-identity and competitive ability. Following this view, a student’s university experience is significantly correlated with the development of his well-being. The development includes the acquisition of knowledge and skills in their field of choice, although it is generally preferable for a student to acquire skills in various fields.  Competent students are those who are well-equipped with knowledge, skills and values that are relevant to current practice. Drawing from this idea, the purpose of this paper is to evaluate students’ challenges, skills, and preparations at the University in facing the IR 4.0 era. A qualitative case study was conducted, employing interviews and document analysis to obtain data from 35 respondents. The respondents were comprised of university students who were selected through purposive sampling. The findings identified several main skills; career and life skills, learning and innovation skills, information, media and technology skills. This study discussed the possible scenarios that might be faced by the students and the university in depth. Based on the findings, proactive measures are needed to encourage students to improve their skills, particularly the skills related to information technology, knowledge, and personal soft skills. Such measures are crucial to fulfil the challenges of IR 4.0.